The Impact of Storage Times of Museum Insect Specimens on PCR Success: Case Study on Moth Collections in Indonesia - HARI SUTRISNO (Bogor Agricultural University, Indonesia, 2012)
Museum specimens are vast repositories of genetic information of interests to biological researchers. Since a new method in DNA extraction, a non destructive method, has been reported to be successful in extracting DNA of museum specimens even fossils without any morphological damages, using museum specimens as resources of genetic information for molecular studies is becoming popular recently. However, the PCR success depends on the quality of the specimens. To evaluate the impact of the storage times of museum specimens on PCR success, we conducted DNA extraction of 14 dry museum specimens of the moths collected from 1992 to 2010 by using a non destructive method. The results showed that the DNA specimens museum were fragmented into various sizes (100-1000 bp) depend on the storage times. On the other hand, fresh specimens which were preserved within absolute ethanol were almost not fragmented. The specimens of < 6 years old (2005-2010) succeed to amplify in 650 bp amplicon but for some specimens of 7 years old (2 of 3 specimens) resulted in a very weak amplification. These specimens, however, were able to amplify strongly in 300 bp amplicon. The results also showed that specimens of 1-19 years old were success to amplify in 100 bp amplicon.